Computer Use and Habitual Spinal Posture in Australian Adolescents - Straker, Leon M. (Association of Schools of Public Health, 2007)
OBJECTIVE. Computer use is common in adolescents, and there is evidence that adolescent spinal posture alters during computer use. However, it is unknown if computer use and habitual postures are associated. The objective of this study was to evaluate associations between adolescent computer use and habitual postures. METHODS. Eight hundred eighty-four adolescents (408 females, 476 males, mean age, 14.0 years, standard deviation, 0.2) completed a questionnaire assessing weekly computer use. Habitual spinal posture was assessed by photographic analysis while standing and sitting. RESULTS. Computer use was associated with adolescent habitual postures. In males, increased computer use was associated with increased head flexion and neck flexion. In females, increased computer use was associated with increased lumbar lordosis. CONCLUSIONS. The amount of weekly computer use was associated with changes in habitual spinal postures, and these depended on gender. These associations may result from temporary computer postures leading to adaptive neuromusculoskeletal changes, though further multivariate and longitudinal studies are needed to confirm causality. As some habitual posture changes may place a greater strain on the musculoskeletal system, computer use by adolescents should be viewed as a possible health concern.